Benign paroxysmal torticollis in infancy - Dimitrijević Lidija; Čolović Hristina; Živković Vesna (Vojnosanitetski Pregled)
Background. Benign paroxysmal torticollis (BPT) is an episodic functional disorder of unknown etiology, characterized by the periods of torticollic posturing of the head, that occurs in the early months of life in healthy children. Case report. We reported two patients with BPT. In the first patient the symptoms were observed at the age of day 20, and disappeared at the age of 3 years. There were 10 episodes, of which 2 were followed by vomiting, pallor, irritability and the abnormal trunk posture. In the second patient, a 12-month-old girl, BPT started from day 15. She had 4 episodes followed by vomiting in the first year. Both girls had the normal psychomotor development. All diagnostical tests were normal. Conclusion. The recognition of BPT, as well as its clinical course may help to avoid not only unnecessary tests and the treatment, but also the anxiety of the parents.